Ordnett, forlaget og brukerne - Eek, Øystein (Nordiske Studier i Leksikografi, 2018)
The article gives a presentation of the interaction between Kunnskapsforlaget and its customers in relation to the dictionary website <www.ordnett.no>. Ordnett was launched in 2004, and is the most widespread commercial dictionary website in Norway. Different tools have been developed to make contact between the publisher and the customers as easy as possible, and the customers give valuable feedback to both the editorial and technical development.